2023
DOI: 10.1002/nop2.1609
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between filial obligation and caregiver depression among adult children: A systematic review and meta‐analysis

Abstract: Aim To explore the relationship between filial obligation and caregiver depression across cultures. Design Systematic review and meta‐analysis. Methods Twelve databases were reviewed for dissertations and peer‐reviewed articles on filial obligation and caregiver depression among adult children, published before January 2020. In total, 476 titles and abstracts were retrieved. Final analysis included six studies; of these, four were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In many Asian countries, deeply ingrained and sometimes explicit legislative norms dictate that the responsibility of caring for older adults family members falls on children and relatives. An exceptional aspect of Asian and particularly Central Asian culture is the practice of multigenerational households, where several generations including grandparents, parents, children, and grandchildren live together (17,48,49). This arrangement often leads to the delegation of caregiving duties to family members, resulting in an underdeveloped system of social and specialized medical support for caregivers (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many Asian countries, deeply ingrained and sometimes explicit legislative norms dictate that the responsibility of caring for older adults family members falls on children and relatives. An exceptional aspect of Asian and particularly Central Asian culture is the practice of multigenerational households, where several generations including grandparents, parents, children, and grandchildren live together (17,48,49). This arrangement often leads to the delegation of caregiving duties to family members, resulting in an underdeveloped system of social and specialized medical support for caregivers (50).…”
Section: Discussionmentioning
confidence: 99%
“…In cultures where there is a strong emphasis on reverence and care for parents or older family members, along with a belief in filial responsibility to provide for their needs, caregiving may not be perceived as highly stressful for caregivers (16,17). However, it is important to acknowledge that these cultural norms, when combined with family expectations and an increased sense of responsibility, can also be stressful for caregivers and even contribute to an elevated risk of experiencing symptoms of depression (18).…”
mentioning
confidence: 99%
“…Three meta-analyses of the association between PFAS and hypertension have been conducted, each also reaching the conclusion that PFAS, particularly PFOA, PFNA, PFHxS, and PFOS, is associated with the risk of hypertension. 92–94…”
Section: Pfas and Cvd Risk Factorsmentioning
confidence: 99%
“…None of the studies reviewed in our previous systematic review provided evidence about the family carers' depressive symptoms in hypertension care. Te result of a systematic review and meta-analysis demonstrated that a stronger perception of flial obligation was associated with increased depressive symptoms among family carers, especially in Chinese culture [66]. Family dyadic relationship-focused interventions can signifcantly improve family carers' depression of patients with stroke, cancer, and arthritis [59].…”
Section: Depressive and Anxiety Symptomsmentioning
confidence: 99%